Experimental study on pore structure and dynamic mechanical properties of modified rubber concrete after freeze-thaw cycle - Minggao Chen; Shujie Yang; Shuyuan Wang; Yan Zhou (Scientific Reports)
Abstract In this paper, the pore structure and mechanical characteristics of freeze-thaw cycled plain concrete, rubber concrete and modified rubber concrete (rubber volume content 10%) under impact load were investigated by using nuclear magnetic resonance instrument and Split Hopkinson Pressure Bar (SHPB) device, and the crack propagation process and fracture morphology characteristics of the specimens were analyzed with high-speed camera device. The test results show that: (1) The T 2 spectra of the rubber concrete specimens showed a three-peak shape under the action of freeze-thaw cycle. The peak value of the main peak of the specimen in freeze-thaw cycle 30, 60, 90 and 120 times is 1.29, 1.53, 1.66 and 1.74 times that of the specimen in freeze-thaw cycle 0 times. The freeze-thaw cycle increased the peak value of T 2 spectrum of the specimen, and the addition of rubber decreased the T 2 spectrum of the specimen, and rubber modification and the reduction of rubber particle diameter made the peak value decrease more significant. (2) The porosity of raw concrete at 0, 30, 60, 90 and 120 freeze-thaw cycles is 11.37%, 15.43%, 17.22%, 19.88% and 21.02%, respectively. With the increase of freeze-thaw cycles, the porosity of the specimens increases continuously. The elastic action of rubber particles can reduce the increase of the internal porosity of concrete under the action of freeze-thaw cycles and reduce the internal porosity of concrete materials. (3) The peak stress and dissipated energy of three kinds of concrete specimens decreased linearly due to freeze-thaw cycle, and the decrease of plain concrete was higher than that of modified rubber concrete. The addition of rubber particles significantly increases the energy absorption effect of concrete, and the modification of rubber particles and the reduction of particle size can further increase the dissipated energy of the specimen. (4) Compared with the plain concrete specimen with zero freeze-thaw cycle, the fractal dimension of the specimen increased by 2.02%, 6.48%, 8.91% and 16.19% when freeze-thaw cycle was 30, 60, 90 and 120 times. The fracture degree of the specimen increased due to freeze-thaw cycle. When freeze-thaw cycle is 120 times, the fractal dimension of each specimen is as follows: plain concrete > 10 mesh rubber concrete > 20 mesh rubber concrete > 30 mesh rubber concrete > 10 mesh modified rubber concrete > 20 mesh modified rubber concrete > 30 mesh modified rubber concrete. The addition of rubber can reduce the crack growth and the degree of fracture and breakage. The research results can provide experimental reference for the safety performance of rubber concrete structures used in cold areas.